Sports Injury Prevention and Rehabilitation : Integrating medicine and science for performance solutions - Joyce, David, 1976-; Lewindon, Daniel (Routledge, Taylor & Francis Group, 2016)
World-class rehabilitation of the injured athlete integrates best practice in sports medicine and physical therapy with training and conditioning techniques based on cutting-edge sports science. In this ground-breaking new book, leading sports injury and rehabilitation professionals, strength and conditioning coaches, biomechanists and sport scientists show how this integrated model works across the spectrum of athlete care. In every chapter, there is a sharp focus on the return to performance, rather than just a return to play